2022
DOI: 10.1007/s11336-022-09841-1
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Tests of Conditional Association for the Assessment of Model Assumptions

Abstract: Many of the models that have been proposed for response data share the assumptions that define the monotone homogeneity (MH) model. Observable properties that are implied by the MH model allow for these assumptions to be tested. For binary response data, the most restrictive of these properties is called conditional association (CA). All the other properties considered can be considered incomplete tests of CA that alleviate the practical limitations encountered when assessing the MH model assumptions using CA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Coincidentally, CA fares well with Spearman's (Spearman, 1904) idea that intelligence tests have positive correlations and together measure a single general intelligence factor, and Guttman's 'first law of intelligence', stating that any two intelligence items have a nonnegative correlation in any population that is "not artificially selected" (Guttman & Levy, 1991), thus suggesting the items should have nonnegative correlations in any subgroup defined by the other items. CA is hard to test fully because it involves many restrictions even for small item sets (De Gooijer & Yuan, 2011;Ligtvoet, 2022;Yuan & Clarke, 2001). Therefore, we will also discuss conditions that are easier to test, such as the condition that the expected item score increases with the rest score, called marginal monotonicity (MM) (Junker, 1993).…”
Section: Testable Conditions Of the Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Coincidentally, CA fares well with Spearman's (Spearman, 1904) idea that intelligence tests have positive correlations and together measure a single general intelligence factor, and Guttman's 'first law of intelligence', stating that any two intelligence items have a nonnegative correlation in any population that is "not artificially selected" (Guttman & Levy, 1991), thus suggesting the items should have nonnegative correlations in any subgroup defined by the other items. CA is hard to test fully because it involves many restrictions even for small item sets (De Gooijer & Yuan, 2011;Ligtvoet, 2022;Yuan & Clarke, 2001). Therefore, we will also discuss conditions that are easier to test, such as the condition that the expected item score increases with the rest score, called marginal monotonicity (MM) (Junker, 1993).…”
Section: Testable Conditions Of the Modelsmentioning
confidence: 99%
“…Junker (1993Junker ( , p. 1372, Junker and Sijtsma (2000) showed that MH ⇒ MM. Ligtvoet (2022) showed that CA ⇒ MM, so MM may be viewed as another incomplete test of CA. MM is an important property because it is conceptually like the idea of a monotone IRF, and for the reader who is unfamiliar with these concepts it may be hard to see how one can have MM without MH.…”
Section: Testable Conditions Of the Modelsmentioning
confidence: 99%
See 3 more Smart Citations